Analysis Of The Role Of The Depok Manpower Office In Developing Human Resources Through Job Training - Liawati, Liawati (Sean Institute, 2025)
This study aims to analyze the role of the Department of Manpower of Depok City in developing human resources (HR) through workforce training programs. This research employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. Interviews were conducted with key informants from the Department of Manpower and training participants to assess the program’s effectiveness. The research findings indicate that the competency-based training programs aim to enhance workforce skills and reduce unemployment rates. The training programs offered are diverse, including barista, culinary arts, vehicle servicing, graphic design, and fashion design, using a 70% practical and 30% theoretical approach. Standardization based on SKKNI ensures training quality, while industrial apprenticeships increase participants’ job opportunities. With simple registration requirements, the program provides greater accessibility for the residents of Depok City. Overall, the Department of Manpower of Depok City plays a significant role in enhancing workforce competitiveness and community welfare, aligning with the city’s development vision.